2022
DOI: 10.1136/annrheumdis-2021-221478
|View full text |Cite
|
Sign up to set email alerts
|

Phase II randomised trial of type I interferon inhibitor anifrolumab in patients with active lupus nephritis

Abstract: ObjectiveTo assess the efficacy and safety of the type I interferon receptor antibody, anifrolumab, in patients with active, biopsy-proven, Class III/IV lupus nephritis.MethodsThis phase II double-blinded study randomised 147 patients (1:1:1) to receive monthly intravenous anifrolumab basic regimen (BR, 300 mg), intensified regimen (IR, 900 mg ×3, 300 mg thereafter) or placebo, alongside standard therapy (oral glucocorticoids, mycophenolate mofetil). The primary endpoint was change in baseline 24-hour urine pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
90
0
5

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 122 publications
(99 citation statements)
references
References 39 publications
4
90
0
5
Order By: Relevance
“…Anifrolumab, a monoclonal antibody to type I interferon receptor, recently became the first FDA-approved medication targeting the interferon pathway in SLE [ 35 ]. A phase 2 trial (NCT02547922) evaluating anifrolumab in LN failed to meet the primary endpoint, but showed numerical improvement, and anifrolumab is now being evaluated in a phase 3 study in LN (NCT05138133) [ 36 ]. IFN-γ is the only member of type II IFN, and plays important roles in innate and adaptive immunity via the activation of chemotactic cytokines (chemokines) [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anifrolumab, a monoclonal antibody to type I interferon receptor, recently became the first FDA-approved medication targeting the interferon pathway in SLE [ 35 ]. A phase 2 trial (NCT02547922) evaluating anifrolumab in LN failed to meet the primary endpoint, but showed numerical improvement, and anifrolumab is now being evaluated in a phase 3 study in LN (NCT05138133) [ 36 ]. IFN-γ is the only member of type II IFN, and plays important roles in innate and adaptive immunity via the activation of chemotactic cytokines (chemokines) [ 34 , 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Anifrolumab, recently approved by the US Food and Drug Administration for the treatment of SLE, is a fully human, IgG1κ monoclonal antibody to the type I interferon receptor subunit 1, and inhibits signaling by all type I interferons (71,72). Anifrolumab is currently being evaluated for LN, and results from a phase II trial will be available later this year (73). While there are no current data regarding the use of anifrolumab in refractory LN, a transcriptomic analysis of protocol kidney biopsies after induction therapy showed that interferon pathway transcripts remained up‐regulated in the kidneys of patients who did not respond to therapy, but declined in patients who had a complete clinical response after induction (74).…”
Section: The Clinical Challengementioning
confidence: 99%
“…Anifrolumab is currently being evaluated for LN, and results from a phase II trial will be available later this year (73). While there are no current data regarding the use of anifrolumab in refractory LN, a transcriptomic analysis of protocol kidney biopsies after induction therapy showed that interferon pathway transcripts remained upregulated in the kidneys of patients who did not respond to therapy, but declined in patients who had a complete clinical response after induction (74).…”
Section: Evidencementioning
confidence: 99%
“…TULIP-LN was a phase II, double-blind RCT investigating the efficacy and safety of an intravenous regimen of two different doses of anifrolumab versus the placebo in a group of 145 subjects with active, biopsy-proven, Class III or IV LN [ 75 ]. As the original TULIP-1 and TULIP-2 trials excluded patients with severe, active LN, TULIP-LN was an RCT that was designed to specifically evaluate the efficacy of anifrolumab in active LN.…”
Section: Biologics Targeting Type I Interferons In Slementioning
confidence: 99%